Sistem Pakar Diagnosis Penyakit Pada Kambing Menggunakan Metode Naive Bayes dan Certainty Factor - Wahyu Rizki Ferdiansyah; Lailil Muflikhah; Sigit Adinugroho (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Examination on goats disease periodically is getting less now, so it makes the goats get diseases easily. This makes breeders have difficulty in the first treatment and the don't know what they should do without an expert. The process of diagnosis of diseases on goats can't be done by just anyone because of the type of disease with symptoms have uncertainty. Based on these problems, the author makes an expert system that is able to diagnosis diseases on goats as usually do an expert. This expert system uses Naive Bayes and Certainty Factor method, PHP programming language and MySQL database. Experimental functional test results show all functional requirements can run well. In addition, the results of system accuracy testing using f-measure method is 86,80%. With the amount of accuracy, expert system diagnosis of goats diseases uses Naive Bayes and Certainty Factor method has a good performance.